2008
DOI: 10.1116/1.3013281
|View full text |Cite
|
Sign up to set email alerts
|

Fluorinated diamondlike carbon templates for high resolution nanoimprint lithography

Abstract: Articles you may be interested inFabrication of silicon template with smooth tapered sidewall for nanoimprint lithography J. Vac. Sci. Technol. B 29, 06FC16 (2011); 10.1116/1.3662094Ultrathin fluorinated diamondlike carbon coating for nanoimprint lithography imprinters Deposition and patterning of diamondlike carbon as antiwear nanoimprint templates Nanoimprint templates were fabricated from diamondlike carbon ͑DLC͒ films grown on Si, using negative-tone e-beam lithography and oxygen plasma etching. An antiadh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…Recent studies have demonstrated the power of this approach, particularly in the study of immune cell function, but more widespread application is currently hampered by the lack of patterning throughput at the appropriate scales. Continued development of high-throughput techniques such as nanoimprint lithography (Guo, 2004; Schvartzman et al, 2008) as well as increased availability of more conventional, optical methods will make these systems available to a wider audience.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated the power of this approach, particularly in the study of immune cell function, but more widespread application is currently hampered by the lack of patterning throughput at the appropriate scales. Continued development of high-throughput techniques such as nanoimprint lithography (Guo, 2004; Schvartzman et al, 2008) as well as increased availability of more conventional, optical methods will make these systems available to a wider audience.…”
Section: Discussionmentioning
confidence: 99%
“…DLC film can be coated on the mold patterns, and nanoscale patterns can be fabricated directly on the DLC surface. A fluorinated DLC mold has low surface energy and is suitable for successful transfer of sub-50-nm patterns [31].…”
Section: Methods For Controlling the Adhesion Energymentioning
confidence: 99%
“…19 PMMA surface fluorination was done in an Oxford PlasmaLab 80 Plus etch system using C 4 F 8 gas as source material. The wafers were initially cleaned by rinsing with acetone and isopropyl alcohol and by exposing them to an oxygen plasma for 1 min (Diener Plasma Etch System).…”
Section: B Substrate Fabricationmentioning
confidence: 99%